Computational structural analysis of 3D printed hip joint implant and comparison of bio-compatible coating materials for design parameters: Coating thickness, hardness, and adhesion requirements. (November 2019) - Uddin, Ghulam Moeen; Nasir, Muhammad Waqar; Arafat, Syed Muhammad; Zubair, Syed Wasim Hassan; Rehman, Abdul; Younis, Muhammad Arslan; Moazam, Sara; Khan, Muhammad Shazad; Niazi, Sajawal Gul; Ashraf, Waqar Muhammad; Adil, Muhammad Taimoor
This research article presents a design parameter assessment technique for three-dimensional printed hip joint implants. A coupled experimental-simulation-based design technique, addressing minimum coating thickness, hardness, and adhesion requirements, is proposed for safe designs of individual three-dimensional printed hip joint implants. The purpose of this study is to analyze the mechanical properties of individual three-dimensional scanned hip joint human bone geometry through numerical simulation and relate these properties to hardness and adhesion values of bio-compatible coatings. The hardness and adhesion experimental results are discussed, which are then related to numerically obtained normal and shear stresses. Finite element analysis on original bone three-dimensional scanned model along with experimental results for investigating the minimum design requirements has not been reported before. Four ceramic coating materials, that is, alumina, CoCrMo, TiN, and zirconia, are discussed for each routine human physical activity. A comprehensive mesh independence study is conducted to ensure that the mesh has no effect on the variation of results. After finite element analysis, it was concluded that the pelvis bone can be taken as a vital bone for recommending design conditions. The finite element results are then coupled with experimental results as the maximum principal stress obtained from the finite element analysis is used to obtain minimum hardness requirements. Similarly, maximum shear stress obtained from the finite element analysis is used to obtain minimum adhesion requirements for three-dimensional printed implants. The coating thickness necessary to obtain minimum hardness and adhesion requirements is then predicted for TiN coating case.